An efficient waveform diversity based on variational mode decomposition of coded beat‐frequency shifted signals algorithm for multiple‐input multiple‐output millimetre‐wave imaging. Issue 10 (24th May 2021) - Molaei, Amir Masoud; Yurduseven, Okan; Fusco, Vincent
Abstract: Waveforms used in multiple‐input multiple‐output (MIMO) systems must be considered in such a way that individual transceiver (T‐R) pairs can be separated from the composite received signal. An algorithm called variational mode decomposition of coded beat‐frequency shifted signals (VMD‐CBFSS) is presented for waveform diversity. First, transmitters are divided into several groups. A small shift is applied to the carrier frequency of the transmitters of different groups. Also, signals within each group are encoded by assigning a binary phase in a time block. On the receiver side, by using a multiresolution analysis technique, the combined signal is decomposed into its main frequency components and then the composite signals of each group are decoded to retrieve each T‐R pair. VMD‐CBFSS provides an efficient solution in terms of overall transmitting time and sampling rate in addition to robustness against channel noise. Moreover, the algorithm is employed in a near‐field MIMO millimetre‐wave imaging system, and results are presented in the form of numerical simulations.